PENGARUH SUPERVISI KEPALA SEKOLAH, KREATIVITAS GURU DAN PERAN SERTA MUSYAWARAH GURU MATA PELAJARAN TERHADAP KINERJA GURU SEKOLAH MENENGAH PERTAMA SE KECAMATAN LENDAH KABUPATEN KULONPROGO (JURNAL ILMIAH TUT WURI HANDAYANI, 2014)
The Influence of Principal Supervising, Teacher’s Creativity, and Participation of Deliberation Subject Teachers on Teachers Performance of Public Junior High School’s of a Lendah Sub-District Kulonprogo Regency. The study was aimed at knowing: (1) the influence of principal supervising, teacher’s creativity and participation of Deliberation Subject Teachers in simultaneous on the teacher’s performance of public junior high schools of Lendah Sub-District Kulonprogo Regency. (2) the influence of supervising principal on the performance of public junior high schools of Lendah Sub-District Kulonprogo Regency, (3). the influence of teacher’s creativity on the teacher’s performance of public junior high schools of Lendah Sub- District Kulonprogo Regency, and (4) the influence of participation of deliberation subject teachers on the teacher’s performance of public junior high schools of Lendah Sub-District Kulonprogo Regency. Correlation descriptive approach was adopted in this study. The research was conducted at junior high schools of a Lendah Sub-District Kulonprogo Regency. Proportionale random sampling was used in the study. Questionnaire was used for collecting the data. The data were analyzed by multiple regression analyses with prerequisite test analysis of normality, linierity, and multicollinearity with degree of significance of 5 %. The study found that : (1) there is a positive significant simultaneous influence of principal supervising, teacher’s creativity, and participation of deliberation subject teachers on the teacher’s performance of public junior high schools of Lendah Sub-District Kulonprogo Regency, (2). there is a positive significant influence of principal supervising on the teacher’s performance of public junior high schools of Lendah Sub- District Kulonprogo Regency, (3) there is a positive significant influence of teacher’s creativity on the teachers’s performance of public junior high schools of Lendah Sub-District Kulonprogo Regency, (4) there is a positive significant influence of participation of deliberation subject teachers on teachers’s performance of public junior high schools of Lendah Sub-District Kulonprogo Regency